An Analysis Of Students’ Difficulties In Learning Listening At The Tenth Grade Of MA Nurul Falah Learning - Irfan Yusuf Amir Faisal (Journal on Education, 2019)
Listening ability is one of the important skills in foreign language learning, and there has been relatively little research in this specific area. The prior English skill is listening. Without passing listening, someone can not be able to speak, read, and write. The present study attempts to investigate the listening problems encountered by a group of Tenth Grade Students of MA Nurul Falah. In this research, the writer uses descriptive research method. Data was gathered by the instruments of observations, students’ listening scores analysis, questionnaires and interviews. The findings of the study showed that there are two listening difficulties factors that the students encountered which are divided to two, those are internal factors such as unclear pronunciation, limited vocabulary, poor knowledge of grammar, unfamiliarity with the listening topic, inability to concentrate, do not like English, self-distrust, speech rate, and accent, the second one are from external factors like poor tapes quality and noises around them while they are listening. The suggestions therefore state that the school should facilitate the listening lab with adequate equipment and the English teachers should motivate students’ enthusiasm by starting to like and learn English listening also extensively outside the classroom.